Effect of exogenous abscisic acid on the formation and release of archeospores in Pyropia yezoensis - Zhang, Li; Gao, Da-Hai; Yan, Xing-Hong (Journal of applied phycology, 2025)
Abscisic acid (ABA) is an important phytohormone, which is involved in plant growth, stress resistance and other physiological processes. To explore the role of ABA in the formation and release of archeospores in Pyropia yezoensis , we first analyzed the effects of exogenous ABA on morphology of gametophytic blades of P. yezoensis . This showed that exogenous ABA treatment significantly increased the release of archeospores and decreased the growth rate of blades, suggesting that ABA had a regulatory effect on the release of archeospores. We further carried out comparative transcriptome analysis of the blades under ABA treatment and found that differentially expressed genes (DEGs) were mainly enriched in metabolic pathways related to antioxidant, such as betalain biosynthesis. In addition, the analysis of ABA signaling pathway candidate genes showed that the expression levels of most genes were increased after exogenous ABA treatment, among which one PP2C gene, py06685 , was significantly upregulated. To explore the relationship between ABA and ROS, the blades were treated with both ABA and ROS inhibitor, with different orders of treatment for the two pharmaceuticals, and this suggested that the effect of ABA on the formation and release of archeospores depended on ROS. Furthermore, the expression levels of genes related to ROS formation was analyzed and the expression level of NOX gene was significantly increased after ABA treatment, suggesting that the promotion effect of ABA on the formation and release of archeospores might depend on ROS. This study provides a preliminary indication that ABA is involved in the regulation of the formation and release of archeospores, but its mechanism needs to be studied.